A COMPARISON OVERVIEW BETWEEN INTERNATIONAL LEGAL INSTRUMENTS AND ALBANIAN LEGISLATION REGARDING THE FIGHT AGAINST CORRUPTION - Dyrmishi, Arsiola (European Scientific Journal, ESJ, 2015)
The promotion and protection of human rights are at the core of legal systems worldwide. Human Rights serve as the basic standard of democracy and rule of law. Recently, human rights generations have been expanding, and it is understable because of the theory of development and social changes. Right to a corruption-free society is at the core of human rights generations. This is because the enjoyment of numerous freedoms and human rights is strongly linked to a corruption-free society. Very important principles such as Equality principle and non-discrimination principle cannot be exercised in a corrupt society. The process of ensuring right to a corruption-free society and punishing corruption when it occurs is a scope of international legal instruments. Numerous legal instruments and legally binding instruments are helping to combat, prevent, and fight corruption as a transnational phenomenon which makes international cooperation essential. Albania has ratified most international instruments, even though it is a crucial case of corruption in Europe because of the high levels of corruption according to statistical data. Is the corruption in Albania caused by the implementation of legal framework? The right to a corruption-free society is part of our constitutional human rights. It is in the administrative law as well as a free-service principle. Also, it enjoys penal protection since penal law sanctions it as a criminal offence. In this research paper, it will be dealt with together with the international legal instruments compared to the three objects of the study of Albanian law (constitutional, administrative, and penal law). This analyzes their legal framework coming to the conclusion as to why the Albanian legislation is not effective in ensuring right to a corruption-free society.